DEVELOPMENT OF KVASS WITH SET PROPERTIES ON THE BASIS OF QFD METHOD - Boris V. Ignatenko; Mikhail N. Eliseev (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article deals with problems of developing high-quality kvass with considerable customer demand. It investigates directions of developing kvass production from the point of view of fast growing food industry: the development of new kvass technologies at the expense of raw material and technological resources, methods of assessment and identification of kvass and new schemes of quality control. The authors point out to the impact of customer demand on innovation development. The method of extending the function of quality QFD to develop new kvass technology advanced by the authors will allow to identify the most important parameters affecting kvass quality.